Nghiên cứu xây dựng hệ thống tính toán hiệu năng cao phục vụ triển khai các bài toán trong Ðại học thông minh - Trương Việt , Phương; Nguyễn Quốc , Hùng; Lê Ngọc , Thạnh; Võ Hà Quang , v (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
Digital transformations in education is a topic attracting a lot of attention from many scientists and researchers in recent times. This transformation helps the computerization of the entire process of education management and assessment of the quality of training services become more favorable. Additionally, digital transformations also improve effectiveness in teaching and learning, especially in E-learning. This is also a premise towards an intelligent ecosystem combining technology with digital-based training services, in which the problem of building smart university is a possible solution. To perform these tasks, it is necessary to have an information technology infrastructure that is strong enough, intelligent enough, and reliable enough to solve problems in the overall framework, in which the construction of a computational system. High Performance Computing will aim to create a foundation for deploying problems with large computational processing needs. However, in some universities in Vietnam, investment in construction and maintenance of such a system faces many difficulties in terms of funding, people... This paper presents a solution to build a high-performance computing system based on available resources using Docker virtualization technology to mobilize computing power from underutilized hardware platforms, defined as a vHPC system. Therefore, this paper proposes an overall perspective when implementing problems smart university.